Legal exceptions to the child’s return in international abduction situations - Castelló Pastor, Juan José (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The Hague Convention of 25 October 1980 on the Civil Aspects of International Child Abduction provides for a system of legal exceptions to the return of the child in order to respect the principle of the best interests of the child. These exceptions to the return or return of the child to the place of residence prior to the illicit transfer as soon as possible must be interpreted restrictively and, of course, the concurrence of the grounds for opposition to the restitution must be proven.The Judgment of the Provincial Court of Las Palmas de Gran Canaria, section 3, of June 21, 2017 object of comment deals with the legal exceptions to the return of the minor and the need to prove the alleged grounds for agreeing the exception. Otherwise, as in the present case, the minor returns to the place of residence prior to the illicit transfer.
Keywords: International child abduction; legal kidnapping; prompt return; The Hague Convention 1980